HUBUNGAN TINGKAT NYERI DENGAN TINGKAT KECEMASAN PADA PASIEN POST OPERASI SECTIO CAESAREA DI RSU PKU MUHAMMADIYAH GOMBONG - Rahmat sumanto; marsito -; ernawati - (Jurnal Ilmiah Kesehatan Keperawatan, 2011)
A post operation will cause pain and anxiety. It needs a talented independent nurse action to overcome those condition. In taking care the patient, nurse must focus in the correlation of the decresing of pain and anxiety. The objective of this research is to find out in the correlation between pain and anxiety level in post sectio caesarea patient in PKU Muhammadiyah Gombong hospital. This is a descriptive correlation research with cross sectional approach. The population were all of post sectio caesarea patients in Rahmah Ward of PKU Muhammadiyah Gombong Hospital. There were 30 respondents taken as the research samples. The variables were pain level as the independent variable and anxiety level of post sectio caesarea patients as the dependent variable. The research used pain scala analog and questioner about anxiety level with HRS-A (Hamilton Rate Scale for Anxiety) that adopted from Nursalam (2003) as the instruments. The result of the research shows that there is a correlation between pain level and anxiety level coefficient = 0.381 with probabailitys value sig 0.038<0.05. It can be concluded  that there is correlation between pain and anxiety level in post sectio caesarea patients in PKU Muhammadiyah Gombong Hospital. Keywords : pain level, anxiety level, post sectio caesarea